The The Talent Identification of Sepak takraw Athletes In Smash Specialization: A Research-based on Analytic Hierarchy Process - Cristy, Florensia; Nurjaya, Dede Rohmat; Hidayat, Rohman (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
Talent identification is a significant investment in sports to determine the proficiency of prospective athletes. This study aims to determine the criteria and sub-criteria in identifying talent for Sepak takraw athletes aged 16 to 19 in smash specialization. This study aims to determine the criteria and sub-criteria in identifying athlete talent resulting from the analytic hierarchy process (AHP) of anthropometric, physiological, and motor variables. Data was collected and analyzed using the Analytic Hierarchy Process (AHP) with Ms. Excel. The method utilized in this research is mixed-methods research, which involves conducting a literature review and providing questionnaires to 30 Sepak takraw experts in Indonesia. This research produces nine sub-criteria, with a high percentage of data analysis results using AHP. These sub-criteria are the top nine sub-criteria consisting of Leg Strength (21.8%), Leg Length (21.1%), Aerobic Power (17.2%), Anaerobic (13.0%), Body Height (873%), Flexibility (6.2%), Agility (5.3%), Body Weight (3.5%) and Aerobic (3.3%). Based on the results of data analysis, there are four most important criteria, specifically Leg Strength from the motor aspect, Aerobic Power and Anaerobic from the physiological aspect, and Body Height from the anthropometric aspect